114k views
5 votes
What is the solution to the equation below sqrt x+3 = x-3

A. 5
B. 6
C. 4
D. 3

1 Answer

1 vote

Answer:

The value of x = 6

Explanation:

Given:

√x + 3 = x - 3

Find:

The value of x

Computation:

Given expression

√x + 3 = x - 3

Squaring both side

(√x + 3)² = (x - 3)²

x + 3 = x² + 3² - (2)(x)(3)

x + 3 = x² + 9 - 6x

x² + 9 - 6x - x - 3 = 0

x² + 7 - 5x = 0

x² - (6 + 1)x + 6 = 0

x² - 6x - x + 6 = 0

x(x - 6) -1(x - 6) = 0

(x - 6)(x - 1) = 0

x = 6 and x = 1

The value of x = 6

User JSchwartz
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.